Congenital duodenal diaphragm with heterotopic pancreas: a case report and literature review - Song, Jinghui; Li, Suolin; Xu, Weili; Sun, Chi; Fang, Yanbin; Gao, Bingzheng; Li, Meng (Frontiers in Pediatrics, 2025)
This case report presents a laparoscopic surgery performed at The Second Hospital of Hebei Medical University for a patient with congenital duodenal diaphragm complicated by heterotopic pancreas (HP). The utilization of indocyanine green (ICG) molecular fluorescent imaging technology and the suspension traction method for duodenal obstruction points during the procedure demonstrates the potential for reducing operational complexity and enhancing surgical success rates. Postoperative feeding via a nasojejunal tube is shown to facilitate rapid restoration of enteral nutrition, mitigate postoperative complications, and decrease the duration of hospitalization.